Influence of planting date on yield components in safflower crop (Carthamus tinctorius L.) in La Pampa (Semiárida, 2019)
The sowing date of the safflower crop varies according to the area and is one of the most important factors in production. The main objective of the work was to establish an optimal planting season to reduce the days elapsed between sowing, germination and emergence, thus decreasing plant losses due to greater exposure to diseases, insects and herbivorous animals, without compromising the components of yield for a time of inadequate planting. The second objective was to expand the information on the harmful insect species as well as the beneficial ones. The study was a with three replications, treatments were Regarding the possible sowing dates in the semiarid Pampas region, the date of mid August (08/15/2014) and mid September (09/18/2014) are those with the highest yields. The date of mid August is recommended because later dates make it more difficult to control weeds due to the conditions of higher temperature and frequently higher level of precipitation. During the crop cycle, sixteen harmful species were identified belonging to the orders: Hemiptera (9 species), Thysanoptera (1 species), Lepidoptera (3 species) and Coleoptera (3 species). As for the beneficial species, seven were found belonging to the orders: Coleoptera (3 species) Hemiptera (1 species), Hymenoptera (2 species) and Araneae (1 species).
Keywords: safflower; sowing dates; yield; insects